100 WOMEN architects in practice. - Harriss, Harriet; House, Naomi; Parrinder, Monika; Ravenscroft, Tom ([S.l.] : RIBA PUBLISHING, 2023)
All the architects in this book deserve international recognition. The reality is, though, that few are household names. Over the last decade, awareness of the need for gender balance in architecture has gained traction. Within the profession, women remain underrepresented, underpromoted and underpaid. Failure to acknowledge women's contribution to the built environment has perpetuated this cycle and impoverished us all. By showcasing 100 exceptional architects - who happen to be women - this book provides a flagship reference to inspire and support everyone working in the profession, no matter how they identify. Global in outlook, the book presents an equitable sample of architects from every continent. We all need heroines as much as heroes. Through illustrated interviews, each woman shares how they are responding to a profound disconnect between architecture and the people and landscape it serves. Their visions, methods and models of leadership are essential to connecting the needs of humans and the planet. In the words of Indigenous Canadian architect Eladia Smoke: Now is a critical time to seek out every opportunity to transmit this knowledge to future generations.' Featuring: 100 interviews with leading women architects, including: Tatiana Bilbao, Odile Decq, Liz Diller, Julia Gamolina, Dorte Mandrup and Farshid Moussavi. Over 400 photographs and drawings. Geographically balanced selection, with profiles across every continent.
Keywords: Women architects; ARCHITECTURE / General